The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Andropause et ménopause : la sexualité sur ordonnance - Moulinié, Véronique (Clio. Femmes, Genre, Histoire, 2013)
L’invention de la ménopause au xixe siècle puis celle de l’andropause dans la seconde moitié du xxe siècle ont eu pour effet d’accroître la surveillance des médecins sur les corps féminins et masculins vieillissants et, plus spécialement, sur la sexualité de cette période de la vie. Or, si ce coup d’état médical a si bien réussi, c’est qu’il a tout autant bénéficié du soutien très actif des femmes que de l’incapacité des hommes à lui résister. C’est aussi qu’il s’inscrivait dans le prolongement de très anciennes pratiques sociales qu’il légitimait. Et qu’on ne s’y trompe pas. Loin de se desserrer, l’étau s’est définitivement refermé. En effet, les hommes, qui ont longtemps tenté d’échapper maladroitement à cette surveillance, ont, aujourd’hui, fini par s’y soumettre, acceptant, de fait, tout le discours silencieux sur les défaillances de leur puissance virile qu’elle suppose.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques